Pengaruh Kualitas Produk Dan Harga Terhadap Kepuasan Pelanggan Jago Coffee Di Wilayah Jakarta Utara - Maharani, Selvi; Setyaningsih, Eka Dyah; Islami, Vina (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
There is an intriguing link between product quality and pricing to investigate because of the reciprocal effect they have on consumer satisfaction. This study's overarching goal is to dissect Jago Coffee in North Jakarta to determine how pricing and product quality interact to maximize consumer happiness. Clients of Jago Coffee in North Jakarta provided the main data. Using questionnaires as a data collecting tool, the researcher picked a sample size of 100 people to interview. The analytical techniques used included tests for reliability and validity as well as tests for multiple linear regression and coefficient of determination. For the purpose of evaluating hypotheses, the t-test and the f-test were used. Collaboratively, the study's independent variables—product quality (9.712>1.660) and price (2.020>1, 660)—had t-values that were higher than the t-table value. Ultimately, consumer satisfaction is a dependent variable, and product quality and price are two independent factors that partly affect it.